Inégalités sociales et enjeux liés à la santé des aînés francophones en situation minoritaire : le cas de l’Atlantique et de l’Acadie des Maritimes - Simard, Majella; Bouchard, Louise (Organisations & Territoires, 2020)
Le vieillissement démographique soulève des enjeux fondamentaux dans la réponse des acteurs sociaux aux besoins manifestés par les aînés sur le plan de la santé. L’objectif de cette contribution est double. Il consiste, d’une part, à identifier les principaux enjeux auxquels sont confrontés les aînés francophones en situation minoritaire sur le plan de la santé et, d’autre part, à examiner la situation des inégalités sociales et les conditions de vie qui en découlent comme déterminant de la santé, de la qualité et de l’accès aux services dans une perspective de développement territorial. Les résultats de notre analyse révèlent que le rapport minoritaire/ majoritaire traduit une inégalité sociale qui, couplée à d’autres déterminants sociaux, contribue de facto à la formation de disparités sur le plan de la santé, d’où la nécessité de mettre en oeuvre une politique à l’endroit des aînés vivant en milieu minoritaire francophone destinée à réduire de tels écarts.

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)
fs-ref-orig: Bouchard, L., Batista, R. et Reaume, M. (2021). Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2021a

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

La santé mentale en contexte francophone minoritaire : état des connaissances - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe (Minorités linguistiques et société, 2024)
Contexte : La communication est une composante essentielle de la relation thérapeutique qui peut être entravée lorsque la culture et la langue de la personne intervenante et du patient diffèrent. En contexte francophone minoritaire, ces problèmes se posent avec acuité dans le domaine de la santé mentale. Objectif : Rendre compte des travaux de recherche effectués sur le thème de la santé mentale et des communautés francophones en contexte linguistique minoritaire. Méthode : Analyse documentaire de 59 publications couvrant la période de 2000 à 2022. Retombées : La synthèse permet de dégager quatre grands constats : a) le processus de désinstitutionnalisation a été à l’origine de la mise en place de politiques linguistiques en santé mentale; b) les données issues des enquêtes canadiennes n’ont contribué que partiellement à améliorer les connaissances sur les états de santé mentale et leurs déterminants; c) l’association entre l’identité culturelle et linguistique et la santé mentale a été explorée, permettant de mieux comprendre des phénomènes comme l’effet du rapport minorité-majorité et de l’insécurité linguistique sur la santé mentale; d) l’accès à des services de santé mentale dans sa langue demeure toujours un défi pour les francophones en contexte minoritaire. Mots-clés : synthèse de littérature, services et politiques en santé mentale, minorité de langue officielle, minorité francophone, Canada

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)
fs-ref-orig: Duong, P., Batista, R., Lizotte, M., Sauvé-Schenk, K. et Bouchard, L. (2024). Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario [infographic]. Data User Conference on Health. Ottawa. fs-code-orig: Duong-2024

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (2025)

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (2025)

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.